In vitroactivity of β‐lactams in combination with avibactam against multidrug‐resistantPseudomonas aeruginosa, Stenotrophomonas maltophiliaandAchromobacter xylosoxidansisolates from patients with cystic fibrosis. Issue 9 (September 2018) - Mathy, Vincent; Grohs, Patrick; Compain, Fabrice
Abstract : N/A: The in vitro activity of anti‐pseudomonal β‐lactams in combination with avibactam was evaluated against 54 multidrug‐resistant non‐fermenting Gram‐negative bacilli isolated from cystic fibrosis patients. Avibactam increased and/or restored the antibacterial activities of ceftazidime and aztreonam against Pseudomonas aeruginosa and Stenotrophomonas maltophilia, respectively. No β‐lactam‐avibactam combination was active against Achromobacter xylosoxidans .